2003
DOI: 10.1590/s1519-566x2003000300022
|View full text |Cite
|
Sign up to set email alerts
|

Neodiplogrammus quadrivittatus (Olivier) (Coleoptera: Curculionidae) no Estado de São Paulo

Abstract: Neotropical Entomology 32(3): 511-512 (2003) Neodiplogrammus quadrivittatus (Olivier) (Coleoptera: Curculionidae) in the State of São Paulo, Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Meanwhile, no evaluations for the S. virgata species were carried out in the late winter/spring period, since there was a high mortality of cuttings in this period caused by an attack of larvae that fed on the inside of the cuttings forming galleries. Sánchez-Soto et al (2003) reported the occurrence of the insect Neodiplogrammus quadrivittatus (Olivier) in S. virgata plants in the state of São Paulo. The occurrence of this insect has also been reported in Sesbania punicea and Cassia corymbosa plants in Rio Grande do Sul state (Silva et al, 1968).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, no evaluations for the S. virgata species were carried out in the late winter/spring period, since there was a high mortality of cuttings in this period caused by an attack of larvae that fed on the inside of the cuttings forming galleries. Sánchez-Soto et al (2003) reported the occurrence of the insect Neodiplogrammus quadrivittatus (Olivier) in S. virgata plants in the state of São Paulo. The occurrence of this insect has also been reported in Sesbania punicea and Cassia corymbosa plants in Rio Grande do Sul state (Silva et al, 1968).…”
Section: Resultsmentioning
confidence: 99%